THE INFLUENCE OF MATERNAL PERSONALITY TRAITS ON INFANT BEHAVIOURAL STYLE: IMPLICATIONS FOR EARLY INTERVENTION - Díaz Herrero, Ángela; Pérez López, Julio; Martínez Fuentes, María Teresa; Herrera Gutiérrez, Eva; Brito de la Nuez, Alfredo G. (Anales de Psicología / Annals of Psychology, 2000)
The aim of the present research was to investigatethe relationships between maternal personality andtheir infants’ temperamental reactions when they are facedboth to social and physical stimuli. For this purpose a sampleof 38 infants and theirs mothers were studied. All newbornswere full-term, without any pre and post-natal complicationand belonging to a middle-class socioeconomicstatus. The mothers filled out the Cattell´s 16PF during thelast trimester of pregnancy. Subsequently, at nine monthsof age, the infants were involved in different laboratorysituations including persons and objects in order to exhibittheir activity level, emotional tone and vocalizations. Theresults indicated that a predictive significant relationshipexists between the maternal extroversion and emotionaltone, activity level and vocalizations showed by theirs infants,when these are faced both to persons and objects.